The Mediating Role of Organizational Trust in the Effect of Social Sustainability on Organizational Resilience: Insights from the Energy Sector - Yazıcı, Ayşe Meriç; Özkan, Ayşegül (Journal of Information and Organizational Sciences, 2024)
The purpose of this study is to explore the mediating role of organizational trust in the impact of social sustainability on organizational resilience. Using a sample of 441 employees in the energy sector in Istanbul, a structured questionnaire was applied to measure employees’ organizational resilience, organizational trust and perceived social sustainability activities. Data analysis was carried out with SPSS and AMOS 24 programs. Factor analysis and structural equation modeling were used in the study. The data analysis based on path modelling confirms the mediating role of organizational trust in the effect of social sustainability on organizational resilience. The findings show that all social sustainability variables significantly affect all organizational trust dimensions, and organizational trust dimensions significantly affect organizational resilience dimensions. Accordingly, organizational trust dimensions and all social sustainability dimensions have a full mediating variable role in the effect of organizational trust dimensions on organizational resilience dimensions. Future research is important to gain a deeper understanding of the relationships between social sustainability, organizational resilience and organizational trust. In particular, studies in specific sectors or cultural contexts can help us better understand how these relationships may vary and how they may shape organizations’ strategies.